A randomized controlled study comparing the objective efficacy and safety of a novel self-inserted disposable vaginal prolapse device and existing ring pessaries - Ziv, Elan; Erlich, Tsvia (Frontiers in Medicine, 2023)
Introduction ProVate is a novel, disposable, collapsible self-inserted vaginal device for the nonsurgical management of pelvic organ prolapse (POP). We assessed possible vaginal microflora changes and POP reduction using ProVate and a commercially available ring pessary (control). Methods We performed post-hoc analysis of data obtained from an interventional, prospective, multicenter, open-label, randomized, controlled, statistically powered (noninferiority), home-use, cross-over study conducted at seven sites. Safety and performance data collected for both devices were analyzed to compare objective POP reduction (employing the Pelvic Organ Prolapse Quantification System [POP-Q]), safety (assessed by the incidence of adverse events [AEs]), and the rates of certain AEs. Results Eighty-five women with symptomatic POP were screened; 71 were randomized, and 58 completed the study per protocol. Forty-nine (90.7%) ProVate users experienced complete prolapse reduction (stage 0), 3 (5.6%) experienced reductions to POP-Q stage 1, and 2 (3.7%%) experienced reductions to stage 2. Collectively, 52/54 (96.3%) ProVate users experienced prolapse reduction to stage 0 or 1. In all, 47/57 (82.5%) control users experienced complete prolapse reduction, while 5 (8.8%), 4 (7.0%), and 1 (1.8%) experienced reductions to stage 1, 2, and stage 3, respectively. Collectively, 52/57 (91.2%) control users experienced reductions to either stage 0 or 1. In 53/54 (98.1%) ProVate and 55/57 (96.5%) control users, there was at least 1 POP-Q stage prolapse reduction, and in 32 (91.4%) ProVate and 31 (83.8%) control users who had stage ≥3 prolapse, there were at least three POP-Q stage reductions. In total, 26/71 (36.6%) ProVate and 22/64 (34.4%) control users in the safety population experienced AEs. The incidence of device-related AEs was 17/71 (23.9%) for ProVate and 13/64 (20.3%) for the control. Most AEs were minor, mild, and anticipated. Conclusion Our analysis demonstrated that ProVate and the control are highly effective in reducing POP, and both are associated with comparably low numbers of AEs. However, ProVate has the advantage of being more user-friendly, suitable for home use, and expected to allow women with POP to practice better and easier self-care.